Relationship between perceived social support and academic well-being based on the mediating role of developmental assets in first-year high school students - Hadis Saeedi; Alireza Manzari Tavakoli; Mitra Kamyabi; Zahra Zeinaddiny Meymand; Mahshid Tajrobehkar (Shahid Beheshti University of Medical Sciences, 2022)
Background: The present study aimed to investigate the relationship between perceived social support and academic well-being considering the mediating role of developmental assets in students. Methods: The present study was applied in terms of aim, descriptive-correlational in term of nature. It was conducted using path analysis approach. The statistical population of the study included the students of the first-year high school in Kerman city in the academic year of 2021-2022. A sample of 300 people (girls and boys) was selected using multi-stage cluster sampling method. The tools of the study were the developmental assets questionnaire, Tuominen-Soini et al., academic well-being questionnaire, and the perceived social support scale. Path analysis was used in Amos Software to analyze the data. Results: The influence of social support on the transformation of academic capital is 0.37 and it is significant at 0.001 level. When people receive support from their families, friends, and other groups that include comfort, respect, love, and interest, it affects their psychological well-being, so all these benefits are actually capital transformations that lead to their well-being. Therefore, the research hypothesis about the relationship between perceived social support and academic well-being through the mediating role of developmental assets in first-year high school students is confirmed. Conclusion: With social support including consolation, affection and care from family, friends and other groups, it is possible to develop and strengthen the developmental assets and finally the academic well-being of students.